DESCRIPTION OF INFLUENCE NEGATIVE STIGMA ON PATIENTS POSITIVE HIV IN NGANJUK - Sony Wahyu Tri Cahyono (Jurnal Ilmu Keperawatan dan Kebidanan, 2017)
ABSTRACT The negative stigma received by HIV positive people is very influential in life. HIV positive people are considered as people who have violated immoral norms in society. HIV positive patients will usually get social sanctions in the form of exclusion, gossip, ridicule, avoided, and even expelled from the community environment. Negative stigma received by HIV positive people not only from the community environment, but there is also a stigma that comes from the family. The form of stigma in the form of discrimination to HIV positive people from family like do not want to eat together, do not want to handshake, do not want to sleep together even do not want to consider family again.This study used qualitative method with phenomenology approach. This study explored the experiences of HIV positive people who get negative stigma from family and society. Participants in this study as many as 5 people. Technique of taking data from informant by using in-depth interview on each participant.This research produces three themes that have been gained from the in-depth interviews. The theme is getting negative stigma from family and society, hiding health status, withdrawing.Factors of the theme found are a description of the effect of negative stigma on HIV positive patients. It is hoped that further research development will improve in the questionnaire to see howfar the negative stigma in HIV positive people is affected.   Keywords: Stigma, and HIV positive